Exploring Project Management Education - Nijhuis, Steven A. (European Journal of Social Science Education and Research, 2023)
The object of this paper is to explore the actual practice in project management education in the Netherlands and compare it to reference institutions and recent literature. A little over 40 percent of the Higher Education institutions in the Netherlands mentions PM education in programs and/or courses. A total of 264 courses, minors and programs in the Netherlands found. In reference institutions 33 courses and programs are found and 36 publications deal with actual teaching of project management in Higher Education. Comparing these sources finds traditional methods of teaching and testing, a roughly comparable focus on subjects and an unsupported high claim of learning level, while the number of credits assigned to project management is relatively small. There is a strong focus on planning without execution, which is critiqued as is the promoted Project Based Learning.